Pengaruh Lingkungan Keluarga, Kemandirian Belajar, dan Media Belajar Terhadap Motivasi Belajar Siswa di MI Babussalam Krian Sidoarjo - Alfiatul Izzati Irawan; Nelud Darajaatul Aliyah; Didit Darmawan (Departement of Mathematics Education, 2024)
In learning activities, motivation can be interpreted as the force that drives student learning activities. This motivation becomes a driving factor within students which drives the learning process which ensures the continuity of learning activities and provides the necessary direction so that the students' desired goals can be achieved. For this reason, this research focuses on the influence of the family environment, learning independence, and learning media on student learning motivation at MI Babussalam, Krian, Sidoarjo. With a population of 650 MI Babussalam students, this research used a sample of 90 grade 6 students. Sampling was carried out randomly to ensure the representativeness of the sample in the larger population. By using a quantitative research design, this research aims to measure and analyze the influence of these variables on student learning motivation. This research produces findings that the family environment, learning independence, and learning media have a significant effect on student learning motivation at MI Babussalam, Krian, Sidoarjo. A conducive family environment, the level of student learning independence and varied learning media can increase student learning motivation at MI Babussalam. These results provide a better understanding of the factors that need to be considered in increasing student learning motivation at the Madrasah Ibtidaiyah level.